CODESRIA Bulletin online, No 2, June 2020: Tanzania Abolishes Public Interest Litigation - Issa G. Shivji, (CODESRIA Bulletin, 2020)
(A Comment on the Amendment of Basic Rights and Duties (Enforcement) Act (Cap. 3 of the Revised Laws of Tanzania) The National Assembly of Tanzania on 10 June 2020 passed the Written Laws (Miscellaneous Amendments Act (No. 3) of 2020. It is a matter of days before the President assents and the amendment becomes the law of the land. The amendment has far-reaching implications for the future of constitutional democracy in the country. In just two sub-sections of the law it purports to abolish Public Interest Litigation (PIL) and to confer sovereign immunity on heads of the Executive, Legislature and the Judiciary. I propose to address these two issues in this short comment. Abolition of PIL Section 4(2) requires that a litigant who files a petition before the court challenging the constitutional validity of an act of the executive or an Act of Parliament states in his/her affidavit accompanying the petition the extent to which the contravention of a fundamental right “has affected such person personally”. This is consistent with Article 30(3) of the Constitution under which a person who alleges that his/her fundamental right has been or is likely to be breached may seek redress in the High Court. In short, the petitioner must show that his/her personal interest is affected over and above the interest of the public. But the amendment goes further. Sub-section 4(3) stipulates: For avoidance of doubt, a person exercising the right provided under Article 26(2) of the Constitution shall abide with the provisions of Article 30(3) of the Constitution. What does Article 26(2) say? Every person has the right … to take legal action to ensure the protection of this Constitution and the laws of the land. Significantly, Article 26(2) appears under the heading ‘Duties to the Society’. To protect the Consti- tution and the laws of the land is therefore not only a right of every person but also his or her consti- tutional duty. In the famous case of Mtikila v Attorney General (1995 TLR 31 (HC)), (which has now become a cause celebre in the East African constitutional ju- risprudence), Judge Lugankingira decided that: Articles 26(2) and 30(3) are independent of each other and enable a citizen to bring a peti- tion under the Constitution in his/her double capacity. As a citizen who seeks to carry out his duty to protect the Consti- tution (under Article 26(2)) or an aggrieved person whose own fundamental right has been breached (under Article 30(3)). (Emphasis supplied) When a public-spirited person or organisation brings a peti- tion under Article 26(2), the matter is in the public interest to vindicate the Constitution and the laws of the This is now well-recognised in many Commonwealth jurisdictions (India, Bangladesh, Pakistan, Ceylon, Singapore, Nigeria, Kenya, Uganda, South Africa and until now Tanzania) in the Global South under the rubric of Public Interest Litigation (PIL). Whereas the doctrine of PIL elsewhere was developed by courts, in Tanzania, Judge Lugakingira decided, it was provided upfront in the con- stitution itself. The following passage in the judgement el- egantly sums up the position: I hold art 26(2) to be an inde- pendent and additional source of standing which can be invoked by a litigant depend- ing on the nature of his claim. Under this provision, too, and having regard to the objective thereof – the protection of the Constitution and legality – a proceeding may be instituted to challenge either the validity of a law which appears to be inconsistent with the Constitu- tion or the legality of decision or action that appears to be con- trary to the Constitution or the law of the land. Personal inter- est is not an ingredient in this provision; it is tailored for the community and falls under the sub-title ‘Duties to the Society.’ It occurs to me, therefore, that art 26(2) enacts into our Consti- tution the doctrine of public in- terest litigation. It is then not in logic or foreign precedent that we have to go for this doctrine; it is already with us in our own Constitution. (paras C, D, E & F, p. 45) (emphasis supplied) Since then Tanzanian courts have recognised PIL and the case of Mtikila has been cited and followed in many African jurisdictions including Kenya, Uganda, South Africa and Malawi. Judge Lugakingira in very ex- plicit terms, for the first time, clearly and unambiguously recognised and underscored the difference between pri- vate and public law and that the rules of locus standi (that is the capacity to bring a mat- ter before the court) of private law do not apply to public law litigation. This was a great advance. Some of the first- generation judges (including such fine judges as Judges Mapigano and Katiti) under- stood the difference between public and private law. They recognised that the practice and procedure in these respective spheres were significantly different. Public law and pri- vate law litigation ought to be approached differently. Judge Mapigano, for instance, con- sistently refused to entertain pleas of many a state attor- ney to apply Civil Procedure Act or Government Proceed- ings Act or rules of evidential standard of proof to judicial review cases. Unfortunately, many of the current generation of members of the Bar and Bench do not fully appreciate the difference between public and private law. Invariably, they fall back on private law procedures and outlook. This is not the place to go into details. Suffice to cite a recent decision of the full bench of the High Court in a constitutional petition1 to illustrate the point I am making. The Court dismissed the petition on a single ground that the petitioner had failed to prove the case beyond reasonable doubt. Rules of standard of proof (beyond reasonable doubt in criminal cases and on balance of probabilities in civil cases) do not apply to the civil side of public law cases, namely constitutional litigation and judicial review applications. In public law litigation, most of the time, the courts are called upon to adjudicate questions of law and not questions of fact. To be sure, even the legal vocabulary used is different. On questions of law, the litigant is called upon to show (and not prove) by argument and precedent to support his/her position that a particular act or law is inconsistent with the Constitution. The amendment obscures the distinction between public and private law in that it seems to apply private law rules of standing to constitutional cases. In my humble view, the amendment under discussion has a three-fold effect. Firstly, it purports to amend the constitution through the back door by making Article 26(2) subject to article 30(3). The fact that the relevant section 4(3) starts with the phrase “for the avoidance of doubt” does not save it because if there was any doubt as to the relation between Articles 26(2) and 30(3), it was made abundantly clear by the Mtikila case which decided that these two provisions of the Constitution were not linked. In my view, section 4(3) is unconstitutional because the Constitution can only be amended by following a special procedure and cannot be amended, either directly or indirectly or under some guise of clarification, by an ordinary Act of Parliament. Secondly, the amendment purports to overrule the court’s decision in the case of Mtikila. It is unusual in self-respecting constitutional democracies to overrule decisions of courts. To overrule or negate the effect of court decisions by legislation amounts to one branch of the state (the legislature) interfering with and usurping the power of the another branch of the state (the judiciary). True, the legislature occasionally does it, particularly in the case of conservative court decisions which strike down progressive reforms of the government of the day. Even so, the Executive through the Legislature rarely resorts to overruling progressive decisions of courts which enlarge the fundamental rights of citizens. It would be socially embarrassing and politically imprudent. It would result in attracting bad reputation in the eyes of citizens of the country and the community of democratic states. Thirdly, without mincing words, it must be pointed out that this legislation marks the end of Public Interest Litigation in the country. This has severe implications for the rights to life, livelihood and dignity of the large majority of working people in villages and urban areas who are the primary victims of unconstitutional and illegal acts of the organs and officials of the state at different levels. Yet as victims of the abuse of power, they do not have the necessary education, capacity or wherewithal to litigate and vindicate their rights and freedoms in courts. Under such circumstances, as Justice Lugakingira said, “if there should spring up a public-spirited individual and seek the Court’s intervention against legislation or actions that pervert the Constitution, the Court, as guardian and trustee of the Constitution and what it stands for, is under an obligation to rise up to the occasion and grant him standing.” (para H, p. 43) Sovereign Immunity Section 4(4) states and this needs to be quoted in full: Where redress is sought against the President, Vice-President, Prime Minister, the Speaker, Deputy Speaker or Chief Justice for any act or omission done in the performance of their duties, a petition shall only be brought against the Attorney General. I must admit at the outset that I fail to gather the intention of the draftsperson behind this section. Is it that the named person cannot be made a respondent in a constitutional litigation even though the alleged wrong has been committed by him or her in his/ her capacity as the occupant of the specified office and in the course of performing his/her duty? If so, how do you frame your cause of action in the petition? Who is the proper party in such a situation? Does the section make the Attorney General a proper party or a necessary party or both? A hypothetical would illustrate the point I am trying to make. XXX is convicted of murder by the High Court on a charge of murder. The presiding judge YYY who conducted the trial and convicted XXX was appointed by the President without prior consultation with the Judicial Service Commission contrary to article 109(2) of the Constitution. XXX wishes to file a Constitutional petition for an order of declaration that his trial and conviction were a nullity because the Court which tried and convicted him was not properly constituted in that the appointment of the presiding judge was invalid being contrary to article 109(2). The proper party to this petition would be the appointing authority, the President, who failed to consult the commission. But under the amendment the President cannot be impleaded. So, the petitioner makes the Attorney General the respondent and pleads in the petition that the President as the appointing authority acted contrary to article 109(2). The petition would be dismissed without fur- ther ado simply because the party whose action is being impleaded is not before the Court and the party, which is before the Court, the Attorney General, did not commit the alleged wrong. The result is that under section 4(4) it is virtually impossible to sue the heads of the three branches of the State even if they are alleged to have breached the constitution or the law of the land in the performance of their constitutional duties. Can we then say that this provision seeks to make the respective heads immune from court proceedings and that a citizen cannot have redress against them? In other words, the named persons can commit wrongs with impunity! This kind of immunity is reminiscent of the monarchical age which followed the adage “the king can do no wrong’, the sovereign is above the law and cannot be impleaded in his own courts? But the president is not a monarch. All the offices mentioned in the section are constitutional offices. The occupants of these of- fices are bound by the constitution and the law of the land. They are not above the law. Their powers and duties are conferred and limited by the law and through the Constitution and the law that they are held accountable to the people. One wonders if the intention of the law was to confer “sover- eign immunity” on the President, Vice-President, Prime Minister, the Speaker, Deputy Speaker and the Chief Justice. If the President had been properly advised by his Attorney General on the implication of this provision, maybe he would have rejected it. Maybe he still will. Concluding Remarks The amendment of the Basic Rights and Duties (Enforcement) Act puts back the clock of constitutional jurisprudence in the country by two decades. In 1984, under the Fifth Constitutional Amendment, the 1977 Constitution for the first time entrenched the Bill of Rights following the Great Constitutional Debate of 1983 which preceded it. The Fifth Constitutional Amend- ment was hailed for ushering in some progressive changes including, among other things, entrenching the local government in the constitution, limiting the presidential tenure to two consecutive terms of five years each, and, of course, en- trenching a fairly progressive Bill of Rights. Since the Bill of Rights became operational in 1987, the higher judiciary developed a pretty progressive constitutional jurisprudence between 1987 and 2015. Roughly beginning 2014, some judges in the higher judiciary have unfortunately adopted a rather conservative approach to human rights cases. Even then, there have been occasional decisions which have not totally forsaken a liberal and purposeful interpretation of fundamental rights. This law, if it is assented to by the President, would have put the final nail in the coffin of declining progressive jurisprudence in the country. Mwalimu Julius Nyerere presciently warned the country of the trend of constitutional amendments which would abridge fundamen- tal rights and freedoms. When the Mtikila case referred to above declared that it was unconstitutional to bar independent or private candidates from standing for elections, the then Government rushed to the Parliament to amend the constitution whose effect was to nullify the judgement. After commenting on the effect of the amendment, Mwalimu exclaimed: This is very dangerous. Where can we stop? If one section of the Bill of Rights can be amended, what is to stop the whole Bill of Rights being made meaningless by qualifications of, and amendments to, all its provisions? (emphasis supplied).2 Notes Centre for Strategic Litigation Ltd. & Change Tanzania Ltd. v. The Attorney General, Regis- trar of Companies & Registrar of NGOs, Civil Cause No 21 of 2019 (High Court), (unreported). Nyerere, J. K., (1995) Our Lead- ership and the Destiny of Tanza- nia, (Harare: African Publishing House), p. 9.